Creation Of Auditor Loyalty: Improving Competence, Quality Of Work And Job Satisfaction - Galih Fajar Muttaqin; Asih Machfuzhoh; Edward Fazri (Universitas Muhammadiyah Malang, 2021)
The purpose of this study is to investigate how auditor competence can affect the work quality and job satisfaction of an auditor which also has an impact on increasing auditor loyalty in carrying out their responsibilities as auditors. This study uses a quantitative method by distributing questionnaires to auditors who work at KAPs domiciled in Banten, Jakarta and Answers. The sample in this study was 170 auditors. Data processing is carried out with a Structural Equation Model (SEM) approach using Partial Least Square (PLS) software. PLS is a component-based or variance-based structural equation (SEM) model. Validity test was carried out using Partial Least Square (PLS) software. The results of this study indicate that the auditor competence, work quality, and job satisfaction can increase the loyalty of auditors working at Public Accounting Firms in Indonesia. This research has implications for the development of audit research, especially the behavior of public accountants, which until now has not been much research that focuses on the behavior of auditors in public accounting firms. In addition, the results of this study can also be used as a reference in determining policies by stakeholders, both regulators and leaders of Public Accounting Firms